The magnetic properties of nanocrystalline Fe-Co(Cr)-Hf-N thin films - Kim, KH; Kim, YH; Kim, J; Han, SH; Kim, HJ (AMER INST PHYSICS, 2000)
We have investigated the effect of Co(Cr) substitution on magnetic properties of as-deposited Fe-Hf-N films. 4 pi Ms increases with increasing Co content (3-16 at. %) and decreases with increasing Cr content. The film Fe56Co16Hf10N18(at. %) shows excellent soft magnetic properties, with 4 pi M(s)similar to 16.8 kG, H(c)similar to 0.25 Oe, and effective permeability similar to 4200 at 100 MHz. In Fe71Cr3Hf9N17, the permeability is about 5200 at 100 MHz, while the values of 4 pi M-s and H-c are similar to 14.6 kG and 0.5 Oe, respectively. In order to estimate the magnetic anisotropy, the angular dependency of the resonance magnetic field and linewidth were observed by ferromagnetic resonance (FMR) at 9.84 GHz. The Fe56Co16Hf10N18 film shows a single resonance peak, whereas the as-deposited Fe-Hf-N films shows weak secondary peaks. (C) 2000 American Institute of Physics. [S0021-8979(00)27908-5].